Zglobalizowana kultura medialna i jej superbohaterowie: serial-killer i terrorysta kamikadze. Patologia ofiarniczej wymiany - Chyła, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2006)
Wojciech Chyła, Superheroes of Globalised Media Culture: Serial Killer and Suicide Bomber. Pathology of Sacrificial Exchange The article analyses the discursive presence of a new type of pop-culture heroes, serial killer and suicide bomber, in the light of contemporary media theory.